Rancang bangun kendali suhu dan kelembaban pada kumbu jamur tiram berbasis Arduino Mega 2560 - Medilla Kusriyanto Kusriyanto; Warindi Warindi; Iyas Pandapotan Siregar (Faculty of Industrial Technology Universitas Islam Indonesia, 2017)
Oyster mushroom is a food fungus with the general characteristics of the body of a white fruit to cream and the hood is semicircular shaped oyster shell with a slightly concave center. Nutritional content of oyster mushrooms are nutritious food ingredients with high protein content, rich in vitamins and minerals, low in carbohydrates, fats and calories. Oyster mushroom growth is strongly influenced by environmental conditions, especially temperature and humidity. In this research will be designed and built automatic temperature and humidity control system on oyster mushrooms to create the right environmental conditions on the cultivation of oyster mushrooms. It uses the DHT 11 sensor as a temperature and humidity sensor to be processed by an arduino mega 2560 microcontroller to condition the environment by watering, hotening and turning on the fan. The system also features data storage media temperature and humidity in the form of SD card and RTC real system for setting up timing of water oyster sprinkler. The results prove that the tool is made to function properly and can be developed as expected. The tool can maintain the temperature around 24° C - 28°C and thehumidity around 79% - 87%.